Keystone and tile, David Sassoon Clocktower - Ghosh, Ayan (2023)
The terracotta keystones on the ground floor arches at the David Sassoon Clock Tower depict the faces of the allegorical figures representing morning, evening, noon, and night, each facing one cardinal direction.